Saikosaponin D Rescues Deficits in Sexual Behavior and Ameliorates Neurological Dysfunction in Mice Exposed to Chronic Mild Stress - Wang, Zhuo; Li, Jianwei; Wu, Wei; Qi, Tao; Huang, Zhansen; Wang, Bo; Li, Shixiong; Li, Chen; Ding, Jiuyang; Zeng, Yuanning; Huang, Peng; Zhou, Zhihua; et al. (Frontiers in Pharmacology, 2021)
Often associated with sexual dysfunction (SD), chronic stress is the main contributing risk factor for the pathogenesis of depression. Radix bupleuri had been widely used in traditional Chinese medicine formulation for the regulation of emotion and sexual activity. As the main active component of Radix bupleuri, saikosaponin D (SSD) has a demonstrated antidepressant effect in preclinical studies. Herein, we sought to investigate the effect of SSD to restore sexual functions in chronically stressed mice and elucidate the potential brain mechanisms that might underly these effects. SSD was gavage administered for three weeks during the induction of chronic mild stress (CMS), and its effects on emotional and sexual behaviors in CMS mice were observed. The medial posterodorsal amygdala (MePD) was speculated to be involved in the manifestation of sexual dysfunctions in CMS mice. Our results revealed that SSD not only alleviated CMS-induced depressive-like behaviors but also rescued CMS-induced low sexual motivation and poor sexual performance. CMS destroyed astrocytes and activated microglia in the MePD. SSD treatment reversed the changes in glial pathology and inhibited neuroinflammatory and oxidative stress in the MePD of CMS mice. The neuronal morphological and functional deficits in the MePD were also alleviated by SSD administration. Our results provide insights into the central mechanisms involving the brain associated with sexual dysfunction. These findings deepen our understanding of SSD in light of the psychopharmacology of stress and sexual disorders, providing a theoretical basis for its potential clinical application.